Tripodal polyamines: Adjustable receptors for cation extraction. Issue 8 (24th May 2018) - Wenzel, Marco; Hennersdorf, Felix; Langer, Matthias; Gloe, Kerstin; Antonioli, Bianca; Buschmann, Hans-Jürgen; Lindoy, Leonard F.; Bernhard, Gert; Gloe, Karsten; Weigand, Jan J.
ABSTRACT: Extraction experiments of a series of tris(2-aminoethyl)amine-based ligands with different aromatic substituents act as efficient extractants for transition metals. Octanol-water distribution measurements, determined stability constants of Ag(I) complexes and Zn(II) extraction studies with different counterions point to the extraction efficiency in dependence of the ligand lipophilicity and the specific structure of the ligand. Competitive extraction experiments showed a selective extraction of Cu(II) from a mixture of Co(II), Ni(II), Cu(II), Zn(II), and Cd(II). Additional hydroxyl groups in (tris(2-hydroxybenzylaminoethyl)amine lead to a loss of this selectivity with extraction yields of 46%, 86% and 97% for Co(II), Ni(II) and Cd(II) ions.